Pengaruh Jahe ( Zingiber Officinale ) terhadap Kadar Glukosa Darah Pada Pasien Diabetes Mellitus Tipe 2 - Alfaritzi Rusli; Herri Sastramihardja; Tryando Bhatara (Universitas Islam Bandung, 2022)
One of the most often grown and utilized medicinal plants is ginger (Zingiber officinale). The essential oils as well as starch in ginger comprise a bioactive compound called Gingerol, Shogaol, Paradol, Zingiberol, and Zingiberin, which has a wide range of effects. In order to find out how ginger (Zingiber Officinale) affects blood glucose level in individuals with type 2 diabetes mellitus, researchers conducted a scoping review. Scoping review was used in this study to gather data from a variety of sources. Glucose levels in patients with type 2 diabetes mellitus were analyzed using samples from international journals on the topic. There were 64,037 articles found in various databases, such as PubMed, ScienceDirect, Springer Link, and Proquest. Six articles were found to be suitable for screening and feasibility testing. As evaluated by blood samples, patients with type 2 diabetes mellitus who ingested ginger had lower levels of HbA1C and insulin sensitivity than those who didn't consume ginger, a scoping analysis of six papers found that ginger ( Zingiber Officinale ) affects to reduce blood glucose level in individuals with type 2 diabetes mellitus, according to the majority of research.